Changes in Cost Incurred by Indonesian Teachers for Online Training during Covid-19 Pandemic - Al Azhar (Populasi, 2020)
Due to Covid-19 transmission, the educational facilities in Indonesia were closed and teachers had to work from home (WFH). It caused face-to-face learning turn into online learning and online training. This study aimed to identify costs incurred by Indonesian teachers for online training during the Covid-19 pandemic. Data collection was carried out by distributing online questionnaires in Google forms to all teachers participating in the online training. Incoming responses were analyzed using SPSS version 26. The results explained that by having self- isolation at home, teachers used their free time to attend online learning. However, they had to pay extra to buy good internet services to properly attend the training. Before the Covid-19 transmission period, the highest internet cost per month was IDR 0-100,000. While during the Covid-19 pandemic, the highest internet expense per month was IDR 100,000-200,000. It was described by the number of respondents who reached 306 respondents (33.85%).